2018
DOI: 10.1177/1420326x18765256
|View full text |Cite
|
Sign up to set email alerts
|

Fungi-induced paint deterioration and air contamination in the Assiut University hospital, Egypt

Abstract: This study aims to evaluate the correlation between fungi causing paint deterioration and air contamination in Assiut University hospital to give a complete picture for the fungal quantity and spectrum. Seventeen fungal species were isolated from 15 samples of deteriorated water-based paint collected from the hospitals. Chaetomium globosum was the most common paint-deteriorating fungal species, followed by Alternaria alternata, Aspergillus parasiticus, Penicillium oxalicum and Setosphaeria rostrata. Direct exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 65 publications
1
3
0
Order By: Relevance
“…However, our results showed that strains of A. flavus had higher I CMC values than P. citrinum. These values suggest a greater potential for wood deterioration for A. flavus (Table 2) compared to previous studies (Abdel-Rahim et al 2018), reporting cellulolytic activity values as high as 0Á88 AE 0Á04 for this micro-organism.…”
Section: Resultssupporting
confidence: 44%
See 1 more Smart Citation
“…However, our results showed that strains of A. flavus had higher I CMC values than P. citrinum. These values suggest a greater potential for wood deterioration for A. flavus (Table 2) compared to previous studies (Abdel-Rahim et al 2018), reporting cellulolytic activity values as high as 0Á88 AE 0Á04 for this micro-organism.…”
Section: Resultssupporting
confidence: 44%
“…These values suggest a greater potential for wood deterioration for A. flavus (Table ) compared to previous studies (Abdel‐Rahim et al . ), reporting cellulolytic activity values as high as 0·88 ± 0·04 for this micro‐organism.…”
Section: Resultsmentioning
confidence: 75%
“…The average indoor temperatures during the seasons of the study period were: winter: 20±2 °C, spring: 25 ±2 °C, summer: 33 ‫؛2±‬ °C, and autumn: 27 ±2 °C. Fans were set off during sampling (Bhatia & Vishwakarma, 2010;Ismail et al, 2018).…”
Section: Samples Collectionmentioning
confidence: 99%
“…Fungi are considered broadly versatile biodeteriogens, being able to thrive in materials and through their synergistic aesthetic, physical and chemical actions contribute to their biodeterioration [5][6][7]. Fungal biophysical biodeterioration can occur by the contraction and expansion of hyphae, leading to the breakdown of the paint film [8,9]. On the other hand, chemical biodeterioration occurs as a result of the action of exoenzymes and organic acids, leading to possible dissolution of the original components of the paint formulation [10,11].…”
Section: Introductionmentioning
confidence: 99%